Association of Type I Neurons Positive for NADPH-Diaphorase with Blood Vessels in the Adult Monkey Corpus Callosum - Rockland, Kathleen S.; Nayyar, Naema (Frontiers in Neural Circuits, 2012)
Sagittal sections through the corpus callosum of adult macaque monkeys (n=7) reveal a subpopulation of neurons positive for NADPH-diaphorase (NADPHd). These are sparsely distributed, with 2-12 neurons scored over the anterior two-thirds of the callosum (about 14 mm). Neurons are densely labeled, type 1; but on the basis of soma and dendritic morphology, these neurons exhibit distinct heterogeneity. In one subpopulation, the cell body is narrowly attenuated (7-10 μm in width). These have bipolar dendrites, extending 300-800 μm from the cell body. One or both of the dendrites is often closely associated with blood vessels and tends to be aligned dorso-ventral, perpendicular to the body of the callosum. Another subpopulation of neurons has a larger soma (typically, 15x20 μm) and more multipolar dendrites, which are not as obviously associated with blood vessels. White matter neurons positive for NADPHd have previously been observed as a transient population, most numerous during development, in the human corpus callosum, as well as in that of other species. Their persistence in the corpus callosum of adult macaques and their close association with blood vessels has not previously been reported and is suggestive of roles other than axon guidance.